DISTRIBUTION OF PLASTIC IN THE NEUSTAL AND BENTHAL OF THE BLACK SEA AND ITS INFLUENCE ON THE ONTOGENESIS OF MARINE BONE FISHES - Виноградов, О.К.; Хуторной, С.О.; Синьогуб, І.О. (SWorldJournal, 2025)
In the process of fish evolution, various ecological and morphological adaptations have been developed, allowing eggs and pre-larvae to passively, and larvae and fry to actively rise and be contained in the hyponeustal of the seas. Good temperature and ox